2021
DOI: 10.21037/apm-21-1777
|View full text |Cite
|
Sign up to set email alerts
|

Issues related to the health status, work pressure and occupational environments of medical staff at level A tertiary public hospitals in Shanghai

Abstract: Background: Medical staff is the main force behind the construction of a healthy China. As a result of increasing social pressure, doctors are at high risk for diseases such as "sudden death" and "overwork death".It is essential that the physical and mental health of medical staff be assessed and long-term mechanisms be introduced to care for medical staff. This study sought to investigate the health status, work pressure, and occupational environments of medical staff at level A tertiary public hospitals in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…With the improvement of knowledge level, medical jobs have increasingly higher requirements on the knowledge and technical level of medical staff, and they can cope with the fierce knowledge competition, deal with the complex interpersonal relationship and the tense social environment by enhancing their competitiveness, which aggravates the occupational stress of highly educated medical staff [ 43 ]. Gao et al [ 44 ] showed that doctoral students consider research pressure as their main work pressure, whereas medical personnel with other degrees consider work intensity as their main work pressure.…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of knowledge level, medical jobs have increasingly higher requirements on the knowledge and technical level of medical staff, and they can cope with the fierce knowledge competition, deal with the complex interpersonal relationship and the tense social environment by enhancing their competitiveness, which aggravates the occupational stress of highly educated medical staff [ 43 ]. Gao et al [ 44 ] showed that doctoral students consider research pressure as their main work pressure, whereas medical personnel with other degrees consider work intensity as their main work pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, almost 60% of the healthcare workers in Ningbo Grade A hospitals work more than 8 h a day, 12.4% more than 10 h a day, and 4.8% more than 12 h a day (31). Overwork is more likely to cause errors or medical disputes, and thus weaken the sense of job security of healthcare workers (32).…”
Section: Discussionmentioning
confidence: 99%
“…We focused on tertiary public hospitals because they have the highest reputation and demand in the Chinese population for specialty care. 22,23 And these providers are also most incentivized to provide DTC telemedicine, claiming the same quality of care against their offline outpatient services.…”
Section: Settingsmentioning
confidence: 99%